Functionalization of cyclic natural rubber grafted maleic anhydride (cnr-g-ma) with variation of ma concentration, inisiator and reaction time - Boy Chandra Sitanggang; Eddyanto Eddyanto (Jurnal Pendidikan Kimia (JPKim), 2019)
Cyclic natural rubber have low compatibilities when mixed with other polymer. The compatibility of a cyclic natural rubber (CNR) could be increased through grafted functional monomer to the polymer backbone. This research aims to know about influence of maleic anhydrate concentration (3-15 phr) as monomer, concentration of benzoyl peroxide (0.05-0.2 molar ratio) as initiator and times (15-90 minute) towards grafting degree of maleic anhydride. The research conducted with reflux in oil bath, at constant temperature 110ºC. The grafting degree determined with titration method and FTIR analysis used to show the existence of grafted maleic anhydrate onto cyclic natural rubber. Result of FTIR analysis showed that grafted anhydrate to cyclic natural rubber assigned with the presence of carbonyl absorptions (C=O stretching). Result titration showed that concentration of maleic anhydrate and benzoyl peroxide enhanced as well as grafting degree. While for variation of time, optimum grafting degree achieved at 60 minute.Keywords: Grafting; inisiator; natural rubber; polymer